Protecting children with ADHD against loneliness: Familial and individual factors predicting perceived child's loneliness. (October 2021) - Laslo-Roth, Roni; George-Levi, Sivan; Rosenstreich, Eyal
Abstract: The present study examined the association between attention-deficit/hyperactivity disorder (ADHD) and the experience of loneliness among school-age children in the context of COVID-19 social restrictions, and was specifically aimed to identify risk and protective factors that might help reduce loneliness. We hypothesized that parents of children with ADHD (compared to without) would perceive their children as experiencing higher levels of loneliness, and that perceived executive functions deficits, parents' social involvement, parental hope, and family cohesion would mediate this relationship. 280 parents of children (166 with ADHD, 114 without) completed questionnaires concerning their child. Children with ADHD were perceived by their parents as lonelier compared to their non-ADHD peers. Individual and parental factors fully mediated the association between ADHD and loneliness. Family cohesion moderated the association between executive function deficits and child's loneliness. We discuss this moderated mediation model in terms of the importance of parental resources for child's well-being in the face of COVID-19-related challenges. Highlights: Children with ADHD were perceived by their parents as lonelier. Child EF fully mediated the association between ADHD and loneliness. Parents involvement and hope mediated the link between child EF and loneliness. Family cohesion moderated the association between child EF deficits and loneliness. Serial mediation and moderated mediation were tested.